PENGARUH PENGAWASAN DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. PRIMANUSA GLOBALINDO PEKANBARU - Nurhayana, Nurhayana (JURNAL ECONOMICA: Media Komunikasi ISEI Riau, 2024)
This research aims to determine the effect of supervision and work discipline on employee performance at PT. Primanusa Globalindo Pekanbaru The types of data used in this research are qualitative data and quantitative data. The population in this study was all 47 employees. The sample in this study was 47 employees or respondents. Data analysis techniques use analytical assumption tests, multiple linear regression analysis and t statistical tests. Research data was collected from respondents and analyzed using linear regression and hypothesis testing. The research results show that supervision has a positive and significant influence on employee performance, with a t-count value (1.679 > 2.673) and organizational culture has a positive and significant influence on employee performance, with a t-count value (1.679 > 2.112).